PENGARUH STRUKTUR KEPEMILIKAN, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Solikin, Ikin; Widaningsih, Mimin; Desmiranti Lestari, Sofie (Program Studi Akuntansi FPEB UPI, 2015)
This study aims to determine whether there is influence of managerial ownership structure, institutional ownership structure, capital structure, and firm size to company value in mining sector companies listed in Indonesia Stock Exchange.The method of this research is descriptive method used to analyze data by way of describing or giving description to the object under study through sample data or population as it is without doing analysis and make conclusion which apply to public. This research uses managerial ownership variable, institutional ownership, capital structure, and firm size as independent variable, and firm value as dependent variable. The population of this study is a mining sector company listed on the Indonesia Stock Exchange in 2010-2012. After going through purposive sampling, obtained 29 companies as sample. The type of data used in this study is secondary data in the form of annual financial statements of the company. The method of analysis used is simple linear regression analysis. Before performing regression test, data analysis test consisted of linearity test and normality test.The results of this study indicate that managerial ownership, capital structure and firm size have a positive effect on firm value. While institutional ownership variable has no positive effect on firm value.